Photoinduced transition-metal and external photosensitizer free cross-coupling of aryl triflates with trialkyl phosphites. Issue 68 (4th August 2021) - Dou, Qian; Geng, Li; Cheng, Bin; Li, Chao-Jun; Zeng, Huiying
Abstract : Photoinduced phosphonation of aryl triflates with trialkyl phosphites via a tandem single-electron-transfer, C–O bond cleavage and Arbuzov rearrangement process in the absence of transition-metal and external photosensitizer is reported. Abstract : Photoinduced phosphonation of aryl triflates with trialkyl phosphites via a tandem single-electron-transfer, C–O bond cleavage and Arbuzov rearrangement process in the absence of transition-metal and external photosensitizer is reported herein. The protocol features good functional group compatibility and mild reaction conditions, providing various aryl phosphates in good to high yields. Furthermore, this strategy allows the late-stage phosphonation of complex and biologically active compounds.